Field-Induced Tomonaga-Luttinger Liquid Phase of a Two-Leg Spin-1/2 Ladder with Strong Leg Interactions - Hong, Tao; Kim, Y. H.; Hotta, C.; Takano, Y.; Tremelling, G.; Turnbull, M. M.; Landee, C. P.; Kang, H. -J.; Christensen, N. B.; Lefmann, Kim; Schmidt, Kai Phillip; Uhrig, G. S.; et al. (Physical Review Letters, 2010)
We study the magnetic-field-induced quantum phase transition from a gapped quantum phase that has no magnetic long-range order into a gapless phase in the spin-1/2 ladder compound bis(2,3-dimethylpyridinium) tetrabromocuprate (DIMPY). At temperatures below about 1 K, the specific heat in the gapless phase attains an asymptotic linear temperature dependence, characteristic of a Tomonaga-Luttinger liquid. Inelastic neutron scattering and the specific heat measurements in both phases are in good agreement with theoretical calculations, demonstrating that DIMPY is the first model material for an S = 1/2 two-leg spin ladder in the strong-leg regime.